Randomised controlled double blind study of role of recombinant erythropoietin in the prevention of chronic lung disease - Griffiths, G. (1997)
AIM—To evaluate the role of recombinant human erythropoietin (R-HuEpo) in reducing iron infusion, which may exacerbate free radical damage, leading to chronic lung disease. METHODS—A multicentre, randomised, placebo controlled, double blind study was carried out in four neonatal intensive care units in Yorkshire. Infants were randomly allocated and received either R-HuEpo (480 U/kg/wk) or placebo by twice weekly subcutaneous injection. The primary outcome measure was the number of days on respiratory support and a secondary outcome the number of blood transfusions required. RESULTS—Forty two very low birthweight (VLBW) infants were randomly allocated. There was little difference in the need for respiratory support one month after randomisation, but subsequently there was a trend towards a reduction in the proportion requiring respiratory support in the R-HuEpo group (difference at three months −0.50, 95% confidence interval −1.00, 0.17). During stay in hospital, the median number of blood transfusions was lower for infants in the R-HuEpo group (difference in medians −2, 95% CI −4, 0). The study was stopped early because of failure to recruit babies at the expected rate. CONCLUSIONS—R-HuEpo seems to reduce the number of days in oxygen for ill VLBW infants. These data could be used to construct a larger multicentre study to evaluate this effect further.   Keywords: human erythropoietin; respiratory support; blood transfusions; chronic lung disease